The Effect of Health Education with Audiovisual Media on Parents' Knowledge about Dental Caries in Elementary School - Priyatno, Hendrik; Rukmana, Nova Mega; Nurdiansyah, Tubagus Erwin (Global Health Science Group, 2024)
SD Negeri 9 Panca Jaya has the highest number of students in the Adi Luhur Health Center's service area and a high incidence of dental problems. In 2022, out of 268 students examined, 185 students (69%) had dental problems. In 2023, out of 384 students examined, 306 students (79.7%) were found to have dental problems. The purpose of this study is to determine the effect of health education using audiovisual media on parents' knowledge about dental caries at SD Negeri 9 Panca Jaya, Mesuji Regency, in 2024. The type of research is quantitative, using a pre-experimental method with a one-group pretest-posttest research design. The study population consists of 226 parents of students in grades 1-3, with a sample size of 70 respondents. The statistical test used is the Wilcoxon Signed Ranks Test. The results of the study showed that the average knowledge of parents before health education at SD Negeri 9 Panca Jaya was 53.07 with a standard deviation of 13.46, with a minimum knowledge score of 25 and a maximum of 80. The average knowledge of parents after the health education was 75.43 with a standard deviation of 10.24, with a minimum knowledge score of 55 and a maximum of 100. The Wilcoxon Signed Ranks Test yielded a p-value of 0.000 (α = 0.05), indicating that p-value < 0.05. Conclusion: There is an effect of health education using audiovisual media on parents' knowledge about dental caries at SD Negeri 9 Panca Jaya, Mesuji Regency, in 2024. Suggestions: It is suggested that the school send messages, information, or images containing health education through class WhatsApp groups, or by posting posters on the prevention of dental caries. Additionally, organizing sessions for students to watch videos about the consequences of poor oral hygiene, accompanied by their parents, is recommended to enhance knowledge and improve the maintenance of children's oral and dental health.